Detection of Human Herpes Virus 8 in Kaposi’s sarcoma tissues at the University Teaching Hospital, Lusaka, Zambia - Tembo, Rabecca (Pan Afr Med J, 2017)
INTRODUCTION: Human herpes virus-8, a γ2-herpes virus, is the aetiological agent of Kaposi sarcoma. Recently, Kaposi's sarcoma cases have increased in Zambia. However, the diagnosis of this disease is based on morphological appearance of affected tissues using histological techniques, and the association with its causative agent, Human Herpes virus 8 is not sought. This means poor prognosis for affected patients since the causative agent is not targeted during diagnosis and KS lesions may be mistaken for other reactive and neoplastic vascular proliferations when only histological techniques are used. Therefore, this study was aimed at providing evidence of Human Herpes virus 8 infection in Kaposi's sarcoma tissues at the University Teaching Hospital in Lusaka, Zambia. METHODS: One hundred and twenty suspected Kaposi's sarcoma archival formalin-fixed paraffin-wax embedded tissues stored from January 2013 to December 2014 in the Histopathology Laboratory at the University Teaching Hospital, Lusaka, Zambia were analysed using histology and Polymerase Chain Reaction targeting the ORF26 gene of Human Herpes virus 8. RESULTS: The predominant histological type of Kaposi's sarcoma detected was the Nodular type (60.7%) followed by the plaque type (22.6%) and patch type (16.7%). The nodular lesion was identified mostly in males (40.5%, 34/84) than females (20.2%, 17/84) (p=0.041). Human Herpes virus 8 DNA was detected in 53.6% (45/84) and mostly in the nodular KS lesions (60%, 27/84) (p=0.035). CONCLUSION: The findings in this study show that the Human Herpes virus-8 is detectable in Kaposi's sarcoma tissues, and, as previously reported in other settings, is closely associated with Kaposi's sarcoma. The study has provided important baseline data for use in the diagnosis of this disease and the identification of the virus in the tissues will aid in targeted therapy.